Study on yield and quality of flowered and non-flowered turmeric (Curcuma longa L.) plants - Kandiannan, K.; Anandaraj, M.; Parthasarathy, Utpala; Thankamani, C.K.; Zachariah, T. John (Journal of Plantation Crops, 2015)
Study on yield and quality of flowered and non-flowered turmeric (Curcuma longa L.) plants